DETECTION OF LATENT INFECTION OF PHYTOPHTHORA INFESTANS IN POTATO SEED TUBERS - Hussain, Touseef; Sharma, Sanjeev; Singh, B P; A, Jeevalatha; Sagar, Vinay; Sharma, Nitya N; Kaushik, S K; Chakrabarti, S K; Anwar, Firoz (Potato Journal, 2013)
Infected seed tubers are an important means of transmission of P. infestans in between potato crops. P. infestans is often brought to the field by latent infected seed tubers. The potato industry currently relies on postharvest, or preplanting, visual disease inspections to detect and sort out the infected tubers to minimise such losses. Disease inspection, however, reveals only established infections and contribution of latent infection to tuber loss is unknown. A diagnostic test that improves on visual inspection to give a rapid and accurate method for specific detection of P. infestans in seed tubers would be of benefit. A PCR based protocol was validated for detection of latent infection in commercial seed tuber stocks. The rapid NaOH tissue assay procedure and specific primer set were used to detect P. infestans from artificially and naturally infected tubers. The percentage of latently infected tubers ranged from 0 to 6.67%. P. infestans was detected by PCR from artificially infected tubers at 4 days post-inoculation with a sensitivity limit of 10 fg of DNA before any visible symptoms appeared on the inoculated tubers. The pathogen could be detected up to 25 mm away from the diseased lesions.